2005
DOI: 10.1021/ja053915s
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Thiolated Au25 Clusters via Ligand Exchange Reactions of Phosphine-Stabilized Au11 Clusters

Abstract: Phosphine-stabilized Au11 clusters in chloroform were reacted with glutathione (GSH) in water under a nitrogen atmosphere. The resulting Au:SG clusters exhibit an optical absorption spectrum similar to that of Au25(SG)18, which was isolated as one of the major products from chemically prepared Au:SG clusters (Negishi, Y. et al. J. Am. Chem. Soc. 2005, 127, 5261). Rigorous characterization by optical spectroscopy, electrospray ionization mass spectrometry, and polyacrylamide gel electrophoresis confirms that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
442
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(471 citation statements)
references
References 20 publications
24
442
3
2
Order By: Relevance
“…Red trace matches well with the previously reported UV-vis spectrum of Au144PET60 cluster 15 and blue trace matches with the UV-vis spectrum of Au25PET18 cluster. 11 The red trace has been vertically shifted for clarity. Inset: Photograph of the TLC plate used for cluster separation (solvent front marked as a dashed line).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red trace matches well with the previously reported UV-vis spectrum of Au144PET60 cluster 15 and blue trace matches with the UV-vis spectrum of Au25PET18 cluster. 11 The red trace has been vertically shifted for clarity. Inset: Photograph of the TLC plate used for cluster separation (solvent front marked as a dashed line).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Most of the reports on such clusters are concerned with gold but a few analogues of silver and copper have also appeared in the literature. [4][5][6][7][8][9][10] Molecules such as Au25SR18, [11][12][13] Au38SR24 14 and Au144SR60 15 are some of the most stable species in this family of materials. Catalytic and biological applications of such materials are fast evolving.…”
Section: Introductionmentioning
confidence: 99%
“…The PL spectrum of H 2 TPPOASH was taken in toluene, whereas that of the clusters was taken in DI water. The PL studies of Au 25 were done in great detail and have been reported recently (36)(37)(38). Emission of Au 25 occurs in the range of 600-800 nm with an emission maximum of 700 nm at 535 nm excitation.…”
Section: Resultsmentioning
confidence: 99%
“…Tsukuda et al (36) characterized the elemental composition of all of the separated entities by ESI-MS and confirmed that the most abundant species is Au 25 (SG) 18 and not Au 28 (SG) 16 , as suggested originally (5). The ligand-exchange reaction of phosphine-stabilized gold clusters (Au 11 ) with GSH gave only Au 25 SG 18 in large yield, suggesting that it is the most stable one among the thiolated clusters from this class (37). Chemical-etching reaction with excess GSH was used to synthesize Au 25 SG 18 in gram scale (38).…”
Section: Introductionmentioning
confidence: 85%
“…Several well defined nanoclusters have been synthesized so far such as Au 20 (SR) 16 , Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 , and Au 144 (SR) 60 . [12][13][14][15][16][17] Among all these thiolate protected gold nanocluster, Au 25 (SR) 18 and Au 144 (SR) 60 are most widely studied due to their higher stability in comparison to other thiolated gold nanocluster. The X-ray crystal structure of the Au 25 (SCH 2 CH 2 Ph) 18 nanocluster was also recently determined in both anionic and neutral forms.…”
Section: Introductionmentioning
confidence: 99%